"Men Are in Front at Eating Time, but Not When It Comes to Rearing the Chicken": Unpacking the Gendered Benefits and Costs of Livestock Ownership in Kenya. Issue 1 (March 2018) - Dumas, Sarah E.; Maranga, Abena; Mbullo, Patrick; Collins, Shalean; Wekesa, Pauline; Onono, Maricianah; Young, Sera L.
Background: Livestock can promote resilience in low-income communities through a number of pathways. Livestock development programs seek to amplify these benefits but often fail to consider the costs to intended beneficiaries or the effect of prevailing gender norms. Objective: To explore perceptions of livestock ownership among female smallholder livestock keepers in Nyanza Region, Kenya, and unpack how the distribution of livestock benefits and investments varies by gender within households. Methods: We used multiple ethnographic techniques, including Photovoice, a photo-elicitation interview method, focus group discussions, and pile sorts, with female smallholder livestock owners (n = 18) participating in an ongoing cohort study. Transcripts were coded using a combination of a priori constructs and grounded theory. Results: We found that livestock benefited households by providing financial security, food security, social benefits, and human time and labor savings. However, these benefits largely promoted long-term household resilience rather than immediate gains. Livestock ownership also had major costs to household time and labor, which were overwhelmingly borne by women and children. Despite this investment, women had limited livestock ownership rights, decision-making power, control over income, or access to meat. Conclusions: Our findings suggest that livestock ownership requires significant investments of household time and labor, which disproportionately burden women. Prevailing gender inequalities may therefore constrain the net benefit of livestock ownership for many women and their households in some contexts. Livestock development programs must assess both program benefits and costs at multiple levels to ensure that women's participation in livestock production leads to improved individual and household outcomes.